Automatic energy demand and system simulation at district level - Verena Weiler; Ursula Eicker (Sustainability Management Forum, 2021)
The importance of climate protection and sustainability is steadily increasing all over the world. However, there is a~large potential for reducing emissions in the heating demand reduction and renewable heat supply of buildings that needs to be addressed. Therefore, a~method was developed within the scope of this work that allows local decision-makers such as energy supply companies, project developers and the public sector to calculate, evaluate and compare different scenarios to make buildings and city districts more sustainable based on few and widely available input data. It includes both the determination of the heat demand and measures for its reduction as well as the selection and simulation of centralised and decentralised supply systems. A~combination of different methods from the fields of geoinformatics, heuristic decision-making and object-oriented modelling is used. The latter forms a~focal point in the work with the development of a~data model for energy system components to enable automatic simulation. The applicability as well as the transferability of the method is shown in several case studies. Based on the simulations results, which can be related to CO2 emissions as well as costs, recommendations for the implementation of measures can be given and implemented. The paper is a~summary of the dissertation with the title “Automatische Simulation von Wärmebedarf und -versorgung auf Quartiersebene” by the first author at Karlsruhe Institute for Technology.
Keywords: 650; Urban simulation; Energy system modelling; Decision making support; CO2 emission reduction